Pengaruh Corporate Governance Terhadap Hubungan Keterlibatan Dewan Di Bidang Politik Dan Manajemen Laba - Yeasy Darmayanti; Dandes Rifa; Irna Khairia (Jurnal Akademi Akuntansi, 2021)
This study aims to analyze the effect of corporate governance on the relationship between board involvement in politics and earnings management in manufacturing companies on the Indonesia Stock Exchange. This study used 63 manufacturing companies which were selected using purposive sampling method. The data analysis method used is multiple regression which is processed through the help of the SPSS program. Based on the results of hypothesis testing, it was found that the board of commissioners involved in politics had a significant positive effect on earnings management. Meanwhile, the board of directors with political connections and corporate governance individually has a significant negative effect on earnings management. In the results of hypothesis testing, it is also found that the board of commissioners and the board of directors who have political connections have a significant effect on earnings management with corporate governance as a moderating variable in manufacturing companies on the Indonesia Stock Exchange. The results of this study found that the implementation of corporate governance will have a different impact on the relationship between the board of commissioners and the board of directors on earnings management. In the relationship between the board of commissioners and earnings management, corporate governance is able to weaken earnings management activities. Meanwhile, in the relationship between the board of directors and earnings management, corporate governance can strengthen earnings management activities.